Transcriptome Signature Reversion as a Method to Reposition Drugs Against Cancer for Precision Oncology. Issue 2 (March 2019) - Koudijs, Karel K. M.; Terwisscha van Scheltinga, Anton G. T.; Böhringer, Stefan; Schimmel, Kirsten J. M.; Guchelaar, Henk-Jan
Abstract : Abstract: Transcriptome signature reversion (TSR) has been hypothesized as a promising method for discovery and use of existing noncancer drugs as potential drugs in the treatment of cancer (i.e., drug repositioning, drug repurposing). The TSR assumes that drugs with the ability to revert the gene expression associated with a diseased state back to its healthy state are potentially therapeutic candidates for that disease. This article reviews methodology of TSR and critically discusses key TSR studies. In addition, potential conceptual and computational improvements of this novel methodology are discussed as well as its current and possible future application in precision oncology trials.